2018
DOI: 10.1108/rege-01-2018-0015
|View full text |Cite
|
Sign up to set email alerts
|

Logistic service quality as a mediator between logistics capabilities and customer satisfaction

Abstract: Purpose A way that companies have found to respond to the challenges of customer satisfaction (CS) is the development logistics services quality. In this sense, the purpose of this paper is to estimate the quality of logistical service as a mediator factor in the relationship between logistics capabilities (LC) and CS. For this, an exploratory survey of the descriptive type was carried out with 117 companies in the Brazilian market of lubricant oil. The collected data, modeled in structural equations, have sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 36 publications
(81 reference statements)
2
37
0
7
Order By: Relevance
“…The findings are also consistent with that of (Yang et al, 2009) which established that liner manufacturing firms' logistics service reliability capability can significantly lead to superior performance. In this study the attributes of logistic service reliability capability had a positive influence on firm performance were speed of service delivery, logistic solutions and reverse logistic operations which concurs with studies elsewhere (Fernandes et al, 2018). While the least attribute that affected firm performance was service provision, follow up on service delivered and client services quality scores suggesting that clients were not satisfied with the quality of services provided by these firms.…”
Section: Firm Performancesupporting
confidence: 86%
See 2 more Smart Citations
“…The findings are also consistent with that of (Yang et al, 2009) which established that liner manufacturing firms' logistics service reliability capability can significantly lead to superior performance. In this study the attributes of logistic service reliability capability had a positive influence on firm performance were speed of service delivery, logistic solutions and reverse logistic operations which concurs with studies elsewhere (Fernandes et al, 2018). While the least attribute that affected firm performance was service provision, follow up on service delivered and client services quality scores suggesting that clients were not satisfied with the quality of services provided by these firms.…”
Section: Firm Performancesupporting
confidence: 86%
“…The dependent variable was firm performance measured using subjective measures of sales volume, profits, market share, customer satisfaction, customer loyalty and new products over the past three years as described in previous research studies (Farris et al, 2010;Santos & Brito, 2012;Hill & Alexander, 2017). The independent variable was logistic service reliability capability was measured based on literature from previously published method (Fernandes et al, 2018). To reduce the effects of confounding variables, the study included two control variables vis: firm size and firm age.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive impact of logistics service on satisfying customers was commonly recognized by (Fernandes et al, 2018;J. Lin, Chen, Kawamura, & Economics, 2016;Ocicka et al, 2016;D.…”
Section: Discussionmentioning
confidence: 99%
“…Archer and Wesolowsky (1996) suggested that service quality and product quality are all of equal importance in affecting customer satisfaction. Fernandes, Moori, and Vitorino Filho (2018) found that logistic service quality was the main variable for customer satisfaction. By evaluating a revised satisfaction and service quality model, Utomo and Rahmawati (2020) studied the link between LSQ and satisfaction.…”
Section: Logistics Service Qualitymentioning
confidence: 99%